VD_FINDINFO Décision / 2011 / 303 vom 30. Juni 2008 - VD Tribunal cantonal (2008)
CONVERSION DE LA PEINE, CONFLIT DE COMPÉTENCES | 36 al. 3 CP, 123 Cst., 2 al. 1 LEP, 27 al. 1 LEP, 38 al. 1 LEP, 363 CPP (CH), 451 CPP (CH)